1978
DOI: 10.1007/bf02291431
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the quantity and quality of colostrum in the cow

Abstract: Logan, E.F., 1978, Factors influencing the quantity and q~ality of colostrum in the cow.Vet. Sci. Commun., 2: 39-46.It is well established that the survival of newborn calves is dependent on their absorbing adequate amounts of maternal immunoglobulin from colostrum.The level of immunity is influenced by the time of feeding after birth and the quantity and quality of the available colostrum.Several factors affect either the quantity or quality of colostrum.The yield of colostrum varies With breed but perhaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This quality decreases as time goes by after birth (7). It has been reported that dairy breeds produce more colostrum than beef breeds and this colostrum is richer in terms of immunoglobulin (4,16). Likewise, in adult ewes and cows, higher levels of colostrum and colostral immunoglobulins have been detected than in youngsters (4,17,18).…”
Section: Factors Affecting the Quality Of Colostrummentioning
confidence: 99%
“…This quality decreases as time goes by after birth (7). It has been reported that dairy breeds produce more colostrum than beef breeds and this colostrum is richer in terms of immunoglobulin (4,16). Likewise, in adult ewes and cows, higher levels of colostrum and colostral immunoglobulins have been detected than in youngsters (4,17,18).…”
Section: Factors Affecting the Quality Of Colostrummentioning
confidence: 99%
“…Their concentration is influenced by the age of dairy cows, breed (Kruse 1970), milking out and suckling colostrum prior to parturition (Logan 1978). The Ig level differs between animals (Messerli and Fey 1973) and is not influenced by the amount of colostrum produced (Logan 1977).…”
mentioning
confidence: 99%